The Relationship Between Athletes' Injury History and Anxiety Levels in Football Games - Rival Caesar Soemantri; Mona Fiametta Febrianty; Mochamad Yamin Saputra (Universitas Negeri Semarang, 2025)
This study aims to explore the relationship between injury history and anxiety levels among soccer players. In sports, anxiety is a psychological factor that significantly impacts an athlete’s mental readiness, concentration, and decision-making ability during a match. A history of injury is often associated with increased anxiety due to the fear of re-injury, and thus, is thought to impact an athlete’s mental state during competition. This study used a quantitative method with a correlational design to assess whether there is a relationship between the two factors. A total of 30 soccer players participated in this study by completing a questionnaire that had been previously tested for effectiveness. The collected data were then analyzed using a correlation test with a significance level of 0.05. The results showed a significance value of 0.32. This result indicates that there is no significant relationship between injury history and anxiety levels among soccer players. Therefore, past injury experience does not play a major role in determining anxiety levels in athletes. These findings suggest that anxiety in sports can be influenced by various other factors, including competitive pressure, competition experience, perception of one’s own abilities, psychological state, and the training environment. Therefore, future research should consider other variables that may have a greater impact on athlete anxiety.